The Lessons of Wrongful Convictions. - Gould, Jon B. (Criminal Justice Ethics)
It is difficult to acknowledge the limitations of a criminal justice process where wrongful convictions can occur without wanting to prevent future errors. Nonetheless, much of the literature concerning wrongful convictions addresses the nature of these errors rather than addressing reforms. Many of those who do address reforms call for the creation of state commissions to investigate wrongful convictions, post-conviction DNA testing, improved practices for eyewitness identification, and the elimination of spurious science in court rooms. The two most pressing reforms are generally accepted to be electronically recording custodial interrogations, and changing eyewitness identification procedures. Getting these reforms enacted, however, will mean appealing to the self-interest of the general populace.